Labor Mobility of Immigrants: Training, Experience, Language and Opportunities - Sarit Cohen; Zvi Eckstein (Institute for the Study of Labor (IZA), 2002)
This paper analyzes the labor mobility and human capital accumulation of male immigrants who moved from the former Soviet Union to Israel. We formulate an estimable dynamic choice model for employment and training in blue and white-collar occupations, where the labor market randomly offered opportunities are affected by past choices. The estimated model well fits the observed patterns of the fast decrease in unemployment as immigrants first find blue-collar jobs and attend training, followed by a gradual movement to white-collar occupations. The estimated rates of return to local training, local experience and local language are very high, but imported skills have zero (conditional) return. Furthermore, the welfare gain from the impact of training on job offer probabilities is larger than it?s effect on wages. Due to low job offer rates, the realized rate of return from white-collar training is relatively low and takes time. As a result, the annual aggregate wage growth, due to the availability of training programs, increases with time in Israel to 1.4 percent in the fifth year.
Keywords: J68; J31; 330; immigration; occupation; training; unemployment; transitions; welfare; Einwanderung; Migranten; Beschäftigungspolitik; Berufsbegleitende Ausbildung; Arbeitsuche; Israel